Moderating role of learning strategies through student assessment of distance learning - Bojana A. Perić Prkosovački (Inovacije u Nastavi, 2024)
The growing use of communication and information technology (ICT) allows for the improvement of distance learning, at the same time challenging teachers to apply ICT effectively in designing interactive lessons which would involve all students as active participants. Students should be able to monitor themselves by self-regulating and exerting control over their learning, taking responsibility, and directing the process. The aim of the research is to explore students’ evaluation of distance learning, as well as the strategies they apply in the learning process, while also determining the connection between their assessment and strategy use. The Student Evaluation of Online Teaching Effectiveness (SEOTE) was used to examine the students’ evaluation of online teaching, while the Motivated Strategies for Learning Questionnaire (MSLQ) was used to examine the use of motivated learning strategies. The results show that students who feel more confident in learning, who set internal goals and are able to self-regulate, evaluate online teaching more positively. Furthermore, students who use cognitive strategies more often rate communication with teachers higher and report spending more time on mastering the content and completing academic assignments. On the other hand, students who experience test anxiety tend to avoid working with peers. These findings imply that students with higher levels of self-efficacy, intrinsic motivation, self-regulation, and strategy use give higher rates to the overall quality of online teaching, while anxiety hinders social interaction and joint learning.